Career Development in the Professions and Semi-Professions in Three Societies - Davis, Kluck Christine (My University, 1978)
The purpose of this thesis is to analyze the career development of four occupations, medicine, law, secondary school teaching and social work, representing three countries - Australia, Canada and Sweden. Based on the literature, it was proposed that at the collective level there would be more consensus in work-related attitudes within the two professions of medicine and law than within the two semi-professions of teaching and social work; and that the professionals would be more homogeneous in terms of their background characteristics than the semi-professionals. At the individual level, it was hypothesized that certain background characteristics such as father's occupation, parents' education, family size and the influence of significant others would be directly related to the age when the career decision was made, as well as the career entry pattern and professional orientation. It was also hypothesized that the age when the career decision was made would be directly related to the career entry pattern and that both would directly affect professional orientation.
Several methods were used to test the propositions and hypotheses, including the comparison of percentage distributions, variances, consensus and homogeneity indices and path analysis. The findings supported both major propositions. There was generally more consensus with respect to work related attitudes among the doctors and lawyers than among the teachers and social workers. In addition, the professionals were more homogeneous than the semi-professionals in terms of background characteristics such as age when the career decision was made, father's occupation and social class identification. At the individual level, the age when the career decision was made was found to be strongly related to the type of career entry pattern in the hypothesized manner. Specifically, respondents who reported earlier career decisions were more likely to enter directly into their career choice. Persons whose fathers had higher SES occupations and who were influenced by close family members usually made earlier career decisions, and in some cases also had more direct entry patterns. Professional orientation was not explained by the variables in the model.
Finally, the 'community' model of the professions which stresses homogeneity among its members is seen as conflicting with a contemporary emphasis on increasing equality of opportunity for entering into the professions, an emphasis which implies increasing heterogeneity.
Keywords: Sociology; Sociology